EVALUATION OF THE IMPLEMENTATION OF EIT-4-BPSD THROUGH MEASUREMENT OF THE ENVIRONMENT AND POLICIES IN NURSING HOMES. (11th November 2018) - Galik, E; Resnick, B; Ellis, J
Abstract: The EIT-4-BPSD incorporates a focus on the assessment and alteration of the environment and policies to assure use of behavioral interventions. The purpose of this study was to test the reliability and validity of The Environment and Policy Assessments in 14 nursing homes. Based on Rasch analysis there was evidence of internal consistency for the Environment Assessment (alpha coefficient of .70) and the Policy Assessment (alpha coefficient of .81). Inter-rater reliability was .58 for the Environment Assessment and .45 for the Policy Assessment. Based on Rasch analysis there was evidence of item fit and construct validity of both measures and a good spread of the items across the full continuum of both concepts. Clarification of definitions of some items is needed to improve reliability. The measures are useful for helping settings assure that the environment and policies support the use of person centered behavioral interventions for BPSD.